Awards for Visual Artists 2001-2002 - Conkelton, Sheryl; Gamblin, Noriko; Hopkins, Terri M.; Linhares, Philip E.; Moseley, Alexander; Moseley, Jaylene (Pasadena : Flintridge Foundation, 2002)
Bartow, Rick ; Carnwath, Squeak ; Connor, Linda ; Agostino, Fernanda D' ; Doolin, James ; Hansen, Gaylen C. ; Henry, Mary ; Howard, Mildred ; Hu, Mary Lee ; Saxe, Adrian ; Toedtemeier, Terry ; Valdez, Patssi
on the occasion of the third biennial cycle of the Flintridge Foundation Awards for Visual Artists
selected exhibitions, selected awards and honors, selected collections, selected bibliography p. 56-61
Engels
boek